Advancing Research and Training on Ageing, Place and Home - Papp, Katalin (Magyar Gerontológia, 2023)
HOMeAGE Doctoral Network Older Adult Reference Group Meeting Horizon Europe (HORIZON) Marie Skłodowska-Curie Actions Doctoral Networks HOMeAGE (101073506)